Hyperdize Jaya Algorithm for Harmony Search Algorithm's Parameters Selection - Alaa A., Al-Omoush; Al-Sewari, Abdul Rahman Ahmed Mohammed; Ameen, Bahomaid; Alamri, Hammoudeh S.; Kamal Z., Zamli (Universiti Malaysia Pahang, 2016)
This paper present a successful method to tune the parameters of the harmony search algorithm, which is a well-known meta-heuristic algorithm. Choosing the values of HS parameters consider as a difficulty when we use it in different cases, and we tried to solve this problem by using another meta-heuristic algorithm to pick the right value for one of these parameters, which is harmony memory consideration rate. To evaluate the performance of the amended algorithm, we have applied it on different bench-mark functions that shows its good performance, in terms of result accuracy in contrast with the original algorithm Harmony Search with less number of iterations, and when we compare it with two other well-known variants of HS.